The Effects of Pilates, Step and Zumba Exercises on Self-esteem, Happiness and Communication Skill Levels - Özdenk, Serhat; İmamoğlu, Mehmet (Asian Journal of Education and Training, 2019)
The aim of this study is to examine the self-esteem, happiness and communication skills of women who participated in pilates, step and zumba exercise programs. A total of 54 women participated in the study. Pilates, step and zumba exercise program was applied three days a week for a total of 12 weeks. As a data col lection tool in research; personal information form, Rosenberg self-esteem scale consisting of 10 items, which was adapted to Turkish by Cuhadaroğlu (1986) the scale of communication skills created by Korkut-Owen and Bugay (2014) consisting of 25 items, and the scale of happiness created by Demirci (2017) composed of 6 items. When the self-esteem, happiness level and communication skills scale scores of the participants in the pilates exercise program are examined, there is a statistically significant difference between the pre-posttest values (p<0.05). When the self-esteem scale scores of the participants in step and zumba exercise program were examined, there was no statistically significant difference between the pre-posttest values (p>0.05). When the happiness level and communication skills scale scores of the participants in step and zumba exercise program were examined, statistically significant difference was observed between the pre-posttest (p<0.05). Pilates exercise program positively affects self-esteem, happiness and communication skills. Step and zumba exercise programs have no effect on self-esteem. Step and zumba exercise program positively affect the level of happiness and communication skills. It is recommended that women participate in exercise programs such as pilates, step and zumba.